Sustainable practices in the hotel sector: a literature review in Latin America. - Aguirre Zamora, Crystal Rubid; Sinforoso Martínez, Saulo (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2026)
OBJECTIVE: To analyze studies conducted in Latin America related to sustainable practice models in the hotel sector, with the purpose of recognizing approaches that drive environmental sustainability in these organizations. MATERIAL AND METHOD: This is a documentary research study with a descriptive scope. A literature review was conducted on 46 research papers from the last five years across various databases, including ResearchGate, Scielo, Redalyc, Dialnet, and indexed journals. RESULTS: The findings show that Mexico positions itself as one of the countries with the highest number of investigations in Latin America regarding sustainable practices. It recorded a total of 20 studies conducted between 2020 and 2025, representing a relative frequency of 43.4% out of 100%, highlighting its leadership in scientific production on sustainability. CONCLUSIONS: More research is required on the topic of sustainable practices in hotels, as their implementation in organizations has been limited to date. However, it generates a competitive advantage for the hotels that apply them, contributing to a sustainable environment. It is concluded that Latin America presents an area of opportunity for developing research on sustainable practices in hotels.